2011
DOI: 10.1007/s00403-010-1117-5
|View full text |Cite
|
Sign up to set email alerts
|

Activation of heparanase by ultraviolet B irradiation leads to functional loss of basement membrane at the dermal–epidermal junction in human skin

Abstract: Recently, we reported that heparanase plays important roles in barrier-disrupted skin, leading to increased interaction of growth factors between epidermis and dermis and facilitating various cutaneous changes, including epidermal hyperplasia and wrinkle formation. However, the role of heparanase in sun-exposed skin remains unknown. Here, we show that heparanase in human keratinocytes is activated by ultraviolet B (UVB) exposure and that heparan sulfate of perlecan is markedly degraded in UVB-irradiated human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
54
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(56 citation statements)
references
References 45 publications
1
54
1
Order By: Relevance
“…with reports of hyperpermeability and angiogenesis in papillary dermis of sun-exposed skin [34,36]. Computer-assisted analysis of CD31-stained sections revealed a 16.1% increase (P = 0.139) in vessel density (Fig.…”
Section: Increase Of Dermal Blood Vessels In Solar Lentigomentioning
confidence: 76%
See 4 more Smart Citations
“…with reports of hyperpermeability and angiogenesis in papillary dermis of sun-exposed skin [34,36]. Computer-assisted analysis of CD31-stained sections revealed a 16.1% increase (P = 0.139) in vessel density (Fig.…”
Section: Increase Of Dermal Blood Vessels In Solar Lentigomentioning
confidence: 76%
“…It has been reported that heparanase in epidermis is activated by UVB exposure [34], and this is associated with angiogenesis and hyperpermeability of blood vessels in dermis [39]. In addition, upregulation of inflammation-related genes in solar lentigo lesions was revealed by means of gene expression profiling analysis [8,40].…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations